A new fossil bristle worm (Annelida: Polychaeta: Aphroditiformia) from the late Cretaceous of tropical America. (30th April 2015) - Luque, Javier; Hourdez, Stéphane; Vinn, Olev
Abstract A new species of aphroditiform polychaete, Protopholoe colombiana, is described from the Coniacian of Colombia, South America, increasing the number of species of this genus known from the fossil record to two. This is the first occurrence of fossil soft-bodied polychaetes in the Tropical Americas, and indicates that aphroditiforms were spread worldwide during the Mesozoic.